Polymorphisms in Pvkelch12 and gene amplification of Pvplasmepsin4 in plasmodium vivax from Thailand, Lao PDR and Cambodia - Duanguppama, J; Mathema, V; Tripura, R; Day, N; Nguon, C; Maxay, M; Von Seidlein, L; Dhorda, M; Peto, T; Nosten, F; White, N; Dondorp, A; et al. (BioMed Central, 2019)
Background Mutations in Pfkelch13 and Pfplasmepsin2/3 gene amplification are well-established markers for artemisinin and piperaquine resistance in Plasmodium falciparum, a widespread problem in the Greater Mekong Subregion (GMS). The Plasmodium vivax parasite population has experienced varying drug pressure dependent on local drug policies. We investigated the correlation between drug pressure from artemisinins and piperaquine and mutations in the P. vivax orthologous genes Pvkelch12 and Pvplasmepsin4 (Pvpm4), as candidate resistance markers. Methods Blood samples from 734 P. vivax patients were obtained from Thailand (n = 399), Lao PDR (n = 296) and Cambodia (n = 39) between 2007 and 2017. Pvkelch12 and Pvpm4 was amplified and sequenced to assess gene mutations. To assess PvPM4 gene amplification, a Taqman® Real-Time PCR method was developed and validated. Selection of non-synonymous mutations was assessed by its ratio with synonymous mutations (Ka/Ks ratios). Mutation rates were compared to the estimated local drug pressure. Results Polymorphisms in Pvkelch12 were rare. Pvkelch12 mutations V552I, K151Q and M124I were observed in 1.0% (7/734) of P. vivax samples. V552I was the most common mutation with a frequency of 0.7% (5/734), most of which (4/5) observed in Ubon Ratchathani, Thailand. Polymorphisms in Pvpm4 were more common, with a frequency of 40.3% (123/305) in 305 samples from Thailand, Lao PDR and Cambodia, but this was not related to the estimated piperaquine drug pressure in these areas (Pearson’s χ2 test, p = 0.50). Pvpm4 mutation V165I was most frequent in Tak, Thailand (40.2%, 43/107) followed by Pailin, Cambodia (43.5%, 37/85), Champasak, Lao PDR (40.4%, 23/57) and Ubon Ratchathani, Thailand (35.7%, 20/56). Pvpm4 amplification was not observed in 141 samples from Thailand and Cambodia. For both Pvkelch12 and Pvpm4, in all areas and at all time points, the Ka/Ks values were < 1, suggesting no purifying selection. Conclusions A novel real-time PCR-based method to assess P. vivax Pvpm4 gene amplification was developed. Drug pressure with artemisinins and piperaquine in the GMS was not clearly related to signatures of selection for mutations in the P. vivax orthologous resistance genes Pvkelch12 and Pvpm4 in areas under investigation. Current resistance of P. vivax to these drugs is unlikely and additional observations including analysis of associated clinical data from these regions could further clarify current findings.